Counseling Service Management in Efforts to Help the Potential Development of High School Students - Muslimah Hikmah Wening; Enung Hasanah (Randwick International of Social Science Journal, 2020)
Management of guidance and counseling services means cooperation to determine, implement, and achieve the goals of guidance and counseling services by implementing planning, organizing, staffing, directing, and leadership and controlling. . Even though the guidance and counseling service program in schools was aimed at helping students to be able to develop optimally, the fact was that there are still many students who are afraid to go to the GC room just to consult with their GC teacher. It was because there is a negative stigma about GC teachers, namely for students.GC teachers were identical to judges at school because they tend to work to solve the problem of student behavior deviations in schools. This study used a qualitative method. The results showed that the process of guidance and counseling services in private schools in urban areas, the participants carried out several stages of activities as a unit of guidance and counseling service activities. These stages were as follows: (1) orientation stage, (2) planning stage. (3) the implementation stage, (4) the evaluation stage.